Youtube As An Agricultural Extension Media - Mujiono Mujiono; Martha Heriniazwi Dianthi (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aims to analyze the meaning of signs in a YouTube video by Penyuluh Pertanian Lapangan titled Pupuk Organik Cair ini 100 Kali Lebih Kuat Dari Air Cucian Beras/Leri - JAKABA SUPER with a duration of 13 minutes and 45 seconds, viewed 2,966,730 times. Methodology: The research adopts a qualitative approach using John Fiske’s semiotics analysis. Results: The video highlights the role of agricultural extension workers as a “bridge” between government policies and farmers. Technical information is conveyed in simple language, supported by clear visuals for better understanding. Findings: The content empowers farmers through relevant, practical education. Structured narration and clean video editing enhance communication effectiveness. Originality: This study emphasizes a semiotic approach in digital agricultural content. Novelty: It provides in-depth analysis of YouTube as an educational medium in agriculture. Conclusion: The video integrates technical education, ecological ideology, and modern technology to promote sustainable farming practices. Type of Paper: Qualitative research paper.